CRIMINAL ACTION IN MANAGEMENT OF ZAKAT, INFAQ AND SHODAQOH - Faisal Riza; Fauzi Anshari Sibarani (Proceeding International Seminar of Islamic Studies, 2022)
Zakat management is carried out by individuals or groups of people who act as Amil Zakat. The centralized management of zakat is in the hands of the government, it is still a debate by looking at the brilliant role of the community in zakat management. Criteria for criminalization of Amil Zakat managers which include punishment must pay attention to its objectives. The application of sanctions as one of the goals of punishment which is concretely poured into a statutory regulation. The purpose of a regulation accompanied by sanctions is that the regulation has the power of effectiveness so that it is obeyed by everyone. Likewise, the Zakat Management the law number 23 of 2011, there are criminal sanctions for parties who commit acts of violations, especially violations of the management of zakat. Therefore, if there are obstacles in the management of zakat, the government can impose criminal sanctions and the like against those who disobey, but when it is connected with Government Regulation Number. 14 of 2014 (PP Number. 14 of 2014) as the implementing regulation of the Law Management of Zakat Number. 23 of 2011. Keywords: Criminal, Zakat, Infaq, Shodaqoh